2014
DOI: 10.5762/kais.2014.15.6.3571
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Intrinsic Motivation on The Relationship Between Positive Psychological Capital, Psychological Empowerment and Creativity

Abstract: This study examined the relationship among PsyCap(positive psychological capital), psychological empowerment, personal creativity and verified the mediated effects of intrinsic motivation in this relationship using the SEM (Structural Equation Model). For this study, the data was collected through on/off-line surveys of members and managers from 12 different enterprises. Among the 418 answers from voluntary participating employees, 332 answers were finally used for statistical analysis. The results were as fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The positive psychological capital construct of Luthans et al (2007a) is an accurate and measurably reliable higher-order, latent multi-dimensional construct. Also, the theory of positive psychology has consistently demonstrated the link between PsyCap (hope, efficacy, resilience, and optimism: HERO) and employees' well-being (Mangundjaya 2012, Siu et al 2015, Youssef-Morgan and Luthans 2015, Gibson and Hicks 2018, subjective well-being (Afzal et al 2016), vocational well-being (Zhao and You 2019), academic motivation (Jafri 2017), employee productivity (Ganotice et al 2016), and intrinsic motivation (Choi and Chang 2014). Rabenu et al (2017) also added that PsyCap was found to have a healthy, positive, and direct correlation with well-being and performance.…”
Section: Psychological Capital or The Hero Modelmentioning
confidence: 99%
“…The positive psychological capital construct of Luthans et al (2007a) is an accurate and measurably reliable higher-order, latent multi-dimensional construct. Also, the theory of positive psychology has consistently demonstrated the link between PsyCap (hope, efficacy, resilience, and optimism: HERO) and employees' well-being (Mangundjaya 2012, Siu et al 2015, Youssef-Morgan and Luthans 2015, Gibson and Hicks 2018, subjective well-being (Afzal et al 2016), vocational well-being (Zhao and You 2019), academic motivation (Jafri 2017), employee productivity (Ganotice et al 2016), and intrinsic motivation (Choi and Chang 2014). Rabenu et al (2017) also added that PsyCap was found to have a healthy, positive, and direct correlation with well-being and performance.…”
Section: Psychological Capital or The Hero Modelmentioning
confidence: 99%